Prevalence of Hypertension and Associated Factors in Dire Dawa City, Eastern Ethiopia: A Community-Based Cross-Sectional Study. (15th May 2019) - Roba, Hirbo Shore; Beyene, Addisu Shunu; Mengesha, Melkamu Merid; Ayele, Behailu Hawulte
Abstract : Background . Hypertension is a major cardiovascular risk factor that is linked with fatal complications and is an overwhelming global challenge. Primary prevention is a key to control hypertension with identification of major risk factors. This study was aimed at assessing the prevalence and factors associated with hypertension. Methods . Community-based cross-sectional study was conducted among 903 adults aged 25 to 64 years in Dire Dawa City, East Ethiopia. Data were collected using World Health Organization (WHO) STEPwise approach to Surveillance (STEPS) for non-communicable disease (NCD) standard survey tool. Multivariate logistic regression models were used to identify relative effects of distal, proximal, and immediate risk factors of hypertension, and all statistical tests were declared significantly at P -value<0.05. Results . The average SBP and DBP were 124.98±17.18 mmHg and 78.92±10.13 mmHg, respectively. The prevalence of hypertension was 24.43% (95% CI: 21.57, 27.28). Majority (51.64%) of adults were not aware of their elevated blood pressure status. hypertension was significantly associated with the age group 30-44 (aOR 3.61, 95% CI: 2.0, 6.55), 45-54 (aOR 5.36, 95% CI: 2.62, 10.91), and 55-64 (aOR 9.38, 95% CI: 4.73, 18.59), being unemployed (aOR 1.68, 95%CI: 1.03, 2.77), ever smoking (aOR 1.89, 95% CI: 1.04, 2.23), having abdominal obesity (aOR 1.72, 95% CI: 1.13, 2.64), and BMI≥25 kg/m 2 (aOR 1.48, 95%CI: 1.01, 2.15). Conclusion . Moderately high prevalence of hypertension was observed among adults in study setting demonstrating a major public health problem. Majority of adults with hypertension in study setting were not aware of their elevated BP status highlighting the burden of the hidden morbidity and subsequent complications. Community level intervention and routine assessment of sociodemographic, behavioral, and biophysiological risk factors, screening, and diagnosis of NCDs should be institutionalized to address the occult burden.